A randomized controlled trial of attention modification for social anxiety disorder. (June 2015) - Carleton, R. Nicholas; Teale Sapach, Michelle J.N.; Oriet, Chris; Duranceau, Sophie; Lix, Lisa M.; Thibodeau, Michel A.; Horswill, Samantha C.; Ubbens, Jordan R.; Asmundson, Gordon J.G.
Highlights: An RCT of a modified attention bias protocol using words to reducing social anxiety. Compares in-lab and at home administrations of the protocol. Active and control conditions resulted in reductions in self-reported social anxiety. No differences were found based on administration location or treatment condition. Abstract: Social Anxiety Disorder (SAD) models implicate social threat cue vigilance (i.e., attentional biases) in symptom development and maintenance. A modified dot-probe protocol has been shown to reduce SAD symptoms, in some but not all studies, presumably by modifying an attentional bias. The current randomized controlled trial was designed to replicate and extend such research. Participants included treatment-seeking adults ( n  = 108; 58% women) who met diagnostic criteria for SAD. Participants were randomly assigned to a standard (i.e., control) or modified (i.e., active) dot-probe protocol condition and to participate in-lab or at home. The protocol involved twice-weekly 15-min sessions, for 4 weeks, with questionnaires completed at baseline, post-treatment, 4-month follow-up, and 8-month follow-up. Symptom reports were assessed with repeated measures mixed hierarchical modeling. There was a main effect of time from baseline to post-treatment wherein social anxiety symptoms declined significantly ( p  < .05) but depression and trait anxiety did not ( p  > .05). There were no significant interactions based on condition or participation location ( p s > .05). Reductions were maintained at 8-month follow-up. Symptom reductions were not correlated with threat biases as indexed by the dot-probe task. The modified and standard protocol both produced significant sustained symptom reductions, whether administered in-lab or at home. There were no robust differences based on protocol type. As such, the mechanisms for benefits associated with modified dot-probe protocols warrant additional research.